Attitudes and practices towards palliative care in chronic heart failure: a survey of cardiovascular nurses and physicians. Issue 1 (4th March 2021) - Singh, Gursharan K.; Ferguson, Caleb; Davidson, Patricia M.; Newton, Phillip J.
Abstract : Background: Heart failure is a chronic condition with various implications for individuals and families. Although the importance of implementing palliative care is recommended in best practice guidelines, implementation strategies are less clear. Aims: This study sought to; (1) determine Australian and New Zealand cardiovascular nurses and physicians' end of life care attitudes and specialist palliative care referral in heart failure and; (2) determine self-reported delivery of supportive care and attitudes towards service names. Methods: An electronic survey was emailed to members of four peak bodies and professional networks. Participants were also recruited through social media. Paper-based versions of the survey were completed by attendees of the 66th Cardiac Society of Australia and New Zealand Annual Scientific Meeting, August 2018. Findings: There were 113 completed responses included in the analyses. Participants were nurses ( n = 75), physicians ( n = 32) and allied health professionals ( n = 4). Most (67%) reported they were comfortable with providing end of life care; however, fewer respondents agreed they received support for their dying patients and one-third experienced a sense of failure when heart failure progressed. Most (84–100%) participants agreed they would refer a heart failure patient later in the illness trajectory. There was a more favourable attitude towards the service name 'supportive care' than to 'palliative care'. Conclusion: Comfort with end of life discussions is encouraging as it may lead to a greater likelihood of planning future care and identifying palliative care needs. Peer support and supervision may be useful for addressing feelings of failure. The use of needs-based assessment tools, adopting the service name 'supportive care' and further research focusing on primary palliative team-based approach is required to improve palliative care access. Impact statement: Cardiovascular nurses and physicians are comfortable providing end of life care, but referrals to palliative care in the later stages of heart failure persists.